Hyponatremia in Acute ST-elevation Myocardial Infarction - A Retrospective Observational Study - CL Aravind; R Ravikiran; Amith Kumar; GK Ranjith Kumar (Wolters Kluwer Medknow Publications, 2024)
Introduction: Hyponatremia is a common electrolyte disorder in hospitalized patients and has been linked to increased morbidity and mortality in various clinical settings. Patients with ST-elevation myocardial infarction (STEMI) are at risk of developing hyponatremia due to complex interplay of pathophysiological mechanisms. This study aimed to investigate the prevalence, risk factors, and prognostic value of hyponatremia in patients with STEMI. Materials and Methods: This was a retrospective study of 192 patients with STEMI who were admitted to a tertiary care hospital between July 2021 and December 2021. Patients were divided into two groups based on their serum sodium levels during hospitalization: Hyponatremia group (serum sodium <135 mEq/L) and normonatremia group (serum sodium ≥135 mEq/L). The prevalence of hyponatremia, demographic variables, ejection fraction, Killip classification, type of STEMI, and in-hospital mortality were compared between the two groups. Results: 20.8% of patients with STEMI had hyponatremia during their hospital stay. Patients with heart failure, lower ejection fraction, and higher Killip classification at admission were more likely to have hyponatremia ([odds ratio (OR): 2.71, 95% confidence interval (CI): 1.23-5.97, P = 0.014], [P = 0.023] and P = 0.002). Patients with lateral STEMI were more likely to have hyponatremia compared to those with other types of STEMI (OR: 2.68, 95% CI: 1.06-6.81, P = 0.037). Patients with hyponatremia had higher in-hospital mortality rate (8 [22.9%], [OR: 4.27, 95% CI: 1.54-11.85, P = 0.005]) and longer hospital stays (P = 0.019) compared to normonatremia group. Conclusion: Hyponatremic patients with STEMI are associated with increased morbidity and mortality. Patients with heart failure, lower ejection fraction, and higher Killip classification at admission should be closely monitored for dyselectrolytemia.